2018
DOI: 10.4103/ijpsym.ijpsym_135_18
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use Patterns, Internet Addiction, and Psychological Distress Among Engineering University Students: A Study from India

Abstract: Background: Internet addiction (IA) among university engineering students and its association with psychological distress can impact their educational progress, academic competence, and long-term career goals. Thus, there is a need to investigate the IA among engineering students. Objectives: This study was a first such attempt to explore internet use behaviors, IA, among a large group of engineering students from India, and its association with psychological distress p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 56 publications
6
40
1
Order By: Relevance
“…In addition, we found that IA increased with age. This is consistent with other studies that revealed usages from internet in younger age related to higher IA,[ 30 ] although they are inconsistent with some other findings. [ 31 32 ] Some study reported more IA in lower age groups.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, we found that IA increased with age. This is consistent with other studies that revealed usages from internet in younger age related to higher IA,[ 30 ] although they are inconsistent with some other findings. [ 31 32 ] Some study reported more IA in lower age groups.…”
Section: Discussionsupporting
confidence: 76%
“…However, with poor self-control, it may become an addictive behavior and may subsequently lead to serious and negative psychosocial effects (e.g., preoccupation and cognitive distortions, worsening social behaviors, and unpleasant feelings or physical discomfort) (6). In addition, there are significant associations between internet-related addiction and poor mental health (e.g., depression, anxiety, and stress) (7)(8)(9). It has further been reported that in China (where the present study was carried out) there is a pooled internet addiction prevalence rate of 7.5% among Chinese adolescents (10) and approximately 11% among college students (11).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of time an individual spends on internet is a crucial factor which increases risk of internet addiction. The research evidence from many studies consistently suggests that the severity levels of IA increase with increasing duration of internet use [2,5] In the present study we noted that use of internet for more than 180 minutes (> 3 hrs) per day and spending more than 200 rupees per month for internet were all associated with internet addiction which is similar to the findings of Thakur A et al who also observed those who spent > 4 hrs/day and spent more money (> 500 Rs/day) for internet usage were found to have a significant association with internet addiction [2] . Limitation of the study: The study lacks the generalizability as it is done in one engineering college in the city.…”
Section: Discussionmentioning
confidence: 99%
“…It is known by different terms such as pathological internet use, problematic internet use, compulsive internet use and internet overuse in the literature [4] . Internet addiction can be described as an individual's inability to control his or her own use of internet causing disturbances and impairment in fulfilment of work, social, and personal commitments [5] . Since 1995, different opinions have been put forward as to whether problematic internet use should be considered as a psychiatric disorder or a mental illness similar to other well established addictive disorders [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation